The Wires of War: Technology and Global Struggle for Power, Jacob Helberg - Areesha Anwar (CISS Insight Journal, 2023)
In the last thirty years, emerging technologies have transformed the character of war. Cyberspace has now become an additional battlefield. Cyberattacks to sabotage a state’s critical infrastructure, cyber espionage to get sensitive information and Internet for fire-hosing or flooding for propaganda and misinformation have posed several new challenges to states’ security. Moreover, the increasing threat of ransomware has become a major concern around the globe. Ransomware attacks on Colonial Gas Pipeline, JBS Meat, and software supply chains such as hacking SolarWinds aggravated cybersecurity concerns across the US. These attacks also led to the issuance of National Security Memorandum to improve cybersecurity for national security by President Biden.